Amelanotic melanoma in the vicinity of acquired melanocytic nevi and not arising from agminated melanocytic nevi: Masquerading as pyogenic granuloma - Angoori Gnaneshwar Rao; V Ashok Babu; Divya Koppada; M Haritha; P Chandana; Swapna; Anoosha (Wolters Kluwer Medknow Publications, 2016)
Amelanotic melanoma (AMM) presenting as pyogenic granuloma and occurring in the vicinity of acquired melanocytic nevi is rare. Herein, we report such a manifestation in a 68-year-old male who presented with the painful red nodule and multiple pigmented patches involving the left great toe. Histopathological examination of skin biopsy taken from the nodule with an immunohistochemical study using HMB45 and S-100 confirmed the diagnosis of AMM. Biopsy from the pigmented patch near the nodule showed features of melanocytic nevus. Investigative work up revealed metastatic deposits in the left inguinal lymph node with no evidence of systemic involvement, placing him in malignant melanoma Stage IIIC of American Joint Committee on Cancer (AJCC) tumor node metastasis system. The development of AMM in the vicinity of acquired melanocytic nevi and manifesting as granuloma pyogenicum is unique in this case.